2007
DOI: 10.1073/pnas.0609783104
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of Wwox reveals a tumor suppressor function

Abstract: The WW domain-containing oxidoreductase (WWOX) spans the second most common fragile site of the human genome, FRA16D, located at 16q23, and its expression is altered in several types of human cancer. We have previously shown that restoration of WWOX expression in cancer cells suppresses tumorigenicity. common fragile site ͉ FHIT ͉ knockout ͉ osteosarcoma ͉ lung cancer T he WW domain-containing oxidoreductase (WWOX) encodes a 46-kDa protein that contains two WW domains and a short-chain dehydrogenase/reductase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
284
6
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(310 citation statements)
references
References 24 publications
18
284
6
2
Order By: Relevance
“…Mammary tumor incidence in C3H-Wwox mice We previously reported that Wwox þ /À mice on B6-129 mixed background develop higher incidence of lung tumors as compared with Wwox þ / þ mice (Aqeilan et al, 2007c). We also noted that some of these mice develop mammary tumors though with very low penetrance (data not shown).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Mammary tumor incidence in C3H-Wwox mice We previously reported that Wwox þ /À mice on B6-129 mixed background develop higher incidence of lung tumors as compared with Wwox þ / þ mice (Aqeilan et al, 2007c). We also noted that some of these mice develop mammary tumors though with very low penetrance (data not shown).…”
Section: Resultsmentioning
confidence: 65%
“…Recently, we generated a mouse carrying a targeted deletion of the Wwox gene (Aqeilan et al, 2007c). Spontaneous osteosarcomas were observed in juvenile Wwox-null mice before their death, whereas targeted loss of one allele increased the incidence of spontaneous and chemically induced lung and forestomach tumors (Aqeilan et al, 2007b, c;Kurek et al, 2010) thus confirming Wwox bona fide tumor suppressor function.…”
Section: Introductionmentioning
confidence: 87%
“…Homozygous deletion of WWOX exons has been found in different cancer cell lines Paige et al, 2000Paige et al, , 2001, and hypermethylation of the WWOX promoter has been detected in both cancer cell lines and primary tumors (Ishii et al, 2003;Kuroki et al, 2004;Iliopoulos et al, 2005). The expression of WWOX is reduced or lost in many different cancers (Aqeilan et al, 2007c). Notably, it has been established that WWOX is inactivated in invasive breast carcinoma (Guler et al, 2004Chang et al, 2005;Nunez et al, 2005;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several tumor types, such as human breast tumors, overexpress aberrant transcripts (Driouch et al, 2002;Ludes-Meyers et al, 2003). Moreover, WWOX has the capacity to function as a tumor suppressor gene both in vitro and in vivo (Bednarek et al, 2001;Kuroki et al, 2004;Fabbri et al, 2005;Iliopoulos et al, 2007;LudesMeyers et al, 2007;Qin et al, 2007;Aqeilan et al, 2007bAqeilan et al, , 2007c. Together, these findings suggest that WWOX is a tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of WWOX expression in breast cancer is associated with a poor clinical outcome for patients (3,4). Although WWOX ectopic expression inhibits tumor growth in different cell types in vitro and in vivo, the targeted ablation of the murine WWOX gene leads to carcinoma (5). Moreover, the incidence of tumor formation in WWOX þ/À mice is significantly higher than in WWOX þ/þ mice.…”
Section: Introductionmentioning
confidence: 96%